How do children and adolescents experience healthcare professionals? Scoping review and interpretive synthesis - Andrew Thompson; Tim Dornan; Richard Conn; Gail Davison; Martina Ann Kelly (BMJ Open, 2021)
Objective Explore children’s and adolescents’ (CADs’) lived experiences of healthcare professionals (HCPs).Design Scoping review methodology provided a six-step framework to, first, identify and organise existing evidence. Interpretive phenomenology provided methodological principles for, second, an interpretive synthesis of the life worlds of CADs receiving healthcare, as represented by verbatim accounts of their experiences.Data sources Five key databases (Ovid Medline, Embase, Scopus, Cumulative Index to Nursing and Allied HealthLiterature (CINAHL) Plus, and Web of Science), from inception through to January 2019, reference lists, and opportunistically identified publications.Eligibility criteria Research articles containing direct first-person quotations by CADs (aged 0–18 years inclusive) describing how they experienced HCPs.Data extraction and synthesis Tabulation of study characteristics, contextual information, and verbatim extraction of all ‘relevant’ (as defined above) direct quotations. Analysis of basic scope of the evidence base. The research team worked reflexively and collaboratively to interpret the qualitative data and construct a synthesis of children’s experiences. To consolidate and elaborate the interpretation, we held two focus groups with inpatient CADs in a children’s hospital.Results 669 quotations from 99 studies described CADs’ experiences of HCPs. Favourable experiences were of forming trusting relationships and being involved in healthcare discussions and decisions; less favourable experiences were of not relating to or being unable to trust HCPs and/or being excluded from conversations about them. HCPs fostered trusting relationships by being personable, wise, sincere and relatable. HCPs made CADs feel involved by including them in conversations, explaining medical information, and listening to CADs’ wider needs and preferences.Conclusion These findings strengthen the case for making CADs partners in healthcare despite their youth. We propose that a criterion for high-quality child-centred healthcare should be that HCPs communicate in ways that engender trust and involvement.